Cost of illness in Charcot-Marie-Tooth neuropathy: Results from Germany. (23rd April 2019) - Schorling, Elisabeth; Thiele, Simone; Gumbert, Laura; Krause, Sabine; Klug, Constanze; Schreiber-Katz, Olivia; Reilich, Peter; Nagels, Klaus; Walter, Maggie C.
Abstract : Objective: To assess cost associated with the disease-specific need of patients diagnosed with Charcot-Marie-Tooth neuropathies (CMT) in Germany. Methods: Patients with CMT were identified through the national patient registry and invited to complete a standardized questionnaire. The data collected include information about health care use, informal care, and other disease-related expenses as well as the working situation. Based on this information, we estimated the annual cost of CMT from the perspective of society. Results: This study included 397 patients with a genetically confirmed CMT diagnosis. We estimated total annual cost of illness (COI) of 22, 362 (95% CI 19, 464–25, 723) per patient, of which 67.3% were direct costs. The highest single cost factor was informal care cost. For Germany, we extrapolated total cost of CMT of 735.0 million (639.8 million–845.5 million). Multivariate regression analysis showed that total annual cost increased with disease severity (Charcot-Marie-Tooth Neuropathy Score). Age, CMT subtype, comorbidities, body mass index, and employment status were also predictors of a change in cost ( p < 0.05). Moreover, we found differences in total cost depending on marital status, subjectively evaluated impairments, dependence on other persons, care level, educational level, and disease duration. Conclusions: CMT is associated with a substantial economic burden. For the first time, the COI of CMT has been assessed and will serve as important input to decision-making in health policy, especially regarding research and development of therapies. Moreover, our results indicate the importance of the patient-reported perception of disease severity related to the consumption of resources.